ALPHABET IN TRADITIONAL INDIAN PAINTING: परंपरागत भारतीय चित्रकला में वर्णविधान - Jain, Sushma (International Journal of Research -GRANTHAALAYAH, 2014)
Indian painting is as elaborate as that of the unlimited payodhi, towards which the ends and depths cannot be easily estimated. The history of primitive creation and its tradition has been created by the footprints of human civilization. Painting is indeed a world of colors. When the colors prevailing in nature become intimate, then the rainbow is formed by the outside and inner colors, the painting is produced by the lines, the shapes are formed by the lines, but the colors attract us more. Art is the name of creating colors prevalent in human consciousness. The first manifestation of his sensations through color and lines, etc., was given by the human etc. In this period, red ocher was the predominance of color, then black, white and sometimes yellow were also used for differentiation. Easily obtained mineral colors have been used in these paintings. These colors mainly use the colors of ocher, ramaraj, hiroji and chariot. 2. These paintings are made directly on the rocks, before their construction, no coating was used, colors were used in both transparent and opaque forms. भारतीय चित्रकला उस निःस्सीम पयोधि की भांति विस्तारित हैं जिसके ओर छोर तथा गहराई का सहज अनुमान नहीं लगाया जा सकता। आदिमकला सृजन एवं उसकी परम्परा का इतिहास मानव सभ्यता के पदचिन्हों द्वारा रचा गया है। चित्रकला वास्तव में रंगो का संसार है। प्रकृति में व्याप्त रंग जब अंतरंग बन जाते है तब बाहर और भीतर के रंगों से जो इंद्रधनुष बनता है वही से चित्रकला उपजती है रेखाओं से आकृतियों का निर्माण होता है लेकिन रंग हमें अधिक आकर्षित करते है। मनुष्य की चेतना में व्याप्त रंगों को रचने का नाम ही कला है1। रंग और रेखाओं के माध्यम से अपनी संवेदनाओं के प्रथम अभिव्यक्ति आदि मानव ने दी इस काल के चित्रों में लाल गेरूए रंग की प्रधानता रही तत्पश्चात् विभिन्नता के लिए काले सफेद तथा कहीं-कहीं पीले रंगों का भी उपयोग किया गया। इन चित्रों में सुगमता से प्राप्त होने वाले खनिज रंगों का उपयोग किया गया है इन रंगों में मुख्यरूप से गेरू, रामरज, हिरोजी तथा खड़िया के रंगों का प्रयोग है2। ये चित्र सीधे शिलाओं पर बने हैं उनके निर्माण से पूर्व किसी भी प्रकार के लेप का प्रयोग नहीं हुआ रंगों का प्रयोग पारदर्शी तथा अपारदर्शी दोनों रूपों में किया गया।